Mechanical behaviour of magnesium nanocomposites at wide range of strain rates and temperatures - Xiao, Jing (2015)
As a result of environmental considerations, a key challenge for the automobile and aerospace industries is to reduce greenhouse gas emissions and to enhance fuel efficiency. This motivates the development of new lightweight alloys as replacement for steel and aluminium alloys. Magnesium and its alloys with low specific weight, high specific strength, vast resources, easy recyclability and biodegradation have attracted extensive interest in recent years. However, the low absolute strength and low ductility limit their usage. It has been found that the addition of stiffer and stronger second-phase reinforcements can enhance strength and ductility of magnesium alloys. Micro-sized reinforcements are effective in enhancing stiffness and strength but accompanied by an obvious decrease in ductility. Recent studies show that it is possible to obtain simultaneous enhancement in strength and ductility when ceramic nanoparticles are employed as reinforcements. The resulting nanocomposites have great potential to replace the existing metals and alloys for various automobile, aerospace and other applications. There are many applications where materials are subjected to high strain rate loading. High strain rate deformation encounters in crash of automobiles or airplanes, where the structural material deforms under various strain rates. In defence and security sector, designing the bomb-proof shields and human protection against bullets and other penetrators need to consider high strain rate deformation of materials. In addition, high strain rate loading also arise in many aspects of everyday life. The dynamic response of a material is quite different from its static response. Limited data is available for high strain rate deformation of magnesium alloy and its nanocomposites, which makes it difficult for widespread usage of these lightweight materials. In the present work, the compressive mechanical response of magnesium alloy AZ31B, AZ31B/0.5%SiC and AZ31B/1.0%SiC to quasi-static and dynamic loading over a wide range of temperature is investigated. The split Hopkinson pressure bar (SHPB) is used to study high strain rate behaviour of the materials in this work. The experimental investigation on the effect of specimen size and pulse shapers has been carried out to decide the optimal specimen dimension and the most suitable pulse shapers used in SHPB tests. The addition of silicon carbide nanoparticles can enhance the strength of the base alloy, while it slightly decreases the ductility of the material. It doesn’t apply to all strain-rate and temperature conditions that higher volume fraction of nanoparticles results in higher strength. But this happens more at higher strain rate. Though ductility becomes worse after adding ceramic nanoparticles, the enhancement of energy absorption capability still exists especially at highest strain rate.